Finding fault lines in long chains of financial information. Issue 5 (3rd September 2019) - Campbell-Verduyn, Malcolm; Goguen, Marcel; Porter, Tony
Abstract: IPE has usefully identified numerous contributors to financial crises. Considerably less attention however has been granted to the roles of financial infrastructures, considered in this special issue as the socio-technical systems enabling basic yet crucial financial functions to be carried out, but that tend to be taken for granted and assumed. This article argues that vulnerabilities in information flows enabled through connections between globally dispersed human actors and non-human objects have shaped the types of events triggering crises, how such periods of instability unfold, and their eventual resolution. Building on insights from actor-network theory, we illustrate how fault lines in 'long chains' of financial information conditioned three financial earthquakes between the 1980s and the present. Our analysis bridges insights from accounts that tend to separately emphasize material and ideational roots of crises. It also points to the importance of supplementing the stress on quantitative indicators with efforts to identify and address vulnerabilities in the quality of connections between disparate actors and objects that enable or disrupt flows of information facilitating global financial markets.